Peran Akademisi Dalam Pemberdayaan Masyarakat Berbasis Kewirausahaan - Solichah, Solichah; Merita, Rona; Fitrotus S, Dewi (Ngaliman: Jurnal Pengabdian Kepada Masyarakat, 2022)
One of the tridharma of higher education is community service, this is one of the social responsibilities of academics. Generally service is manifested in the form of community empowerment. Concrete manifestations of the role of academics in community empowerment include being an idea contributor, a facilitator or community assistant, and an "advocate" for various community interests. The purpose of this research is how the role of academics in community empowerment through mentoring and entrepreneurship training as the foundation of the community to live independently. In principle, academics in everyday life will coexist with society. The results of this study are the introduction of entrepreneurship directly in the field as an effort to strengthen the mental as well as prepare new human resources who are more creative, innovative and progressive in the future.